A new method based on charge parameters to analyse the performance of stand-alone photovoltaic systems - Muñoz, F.J.; Almonacid, G.; Nofuentes, G.; Almonacid, F.
The monitored data in photovoltaic systems are processed to determine overall energy balances which, together with the energy efficiencies and indices of performance, give a good indication of the performance of PV systems. However, the analysis based on energy parameters shows some shortcomings when they are used to analyse the performance of stand-alone photovoltaic (SAPV)systems, especially those without Maximum Power Point Tracker (MPPT). This kind of systems represents a large percentage of the SAPV systems (e.g. demonstration projects, consumer and industrial applications, Solar Home Systems in developing countries, etc.). This paper tries to give an alternative method that manages to analyse this kind of systems in a better way. This method is based on a translation of the energy parameters given by the Joint Research Center and the IEC Standard 61724 into new charge-related parameters. It must be said that charge parameters can be used by themselves to evaluate the system performance. Therefore, it is not necessary to deduce energy parameters using the nominal battery voltage. The monitored data of two SAPV systems without MPPT are used to compare the performance of these systems based on energy parameters with the analysis provided by the new charge parameters. This study will highlight the advantages of the charge parameters method.
Keywords: MONITORING; STAND-ALONE PV SYSTEMS; PERFORMANCE